Strategi Peningkatan Literasi Keuangan Syariah dalam Pengembangan Kinerja UMKM di Desa Rondaman - Rahmi Siregar; Harfandi Harfandi (ARZUSIN, 2026)
This study was motivated by the low level of Islamic financial literacy among micro, small, and medium enterprises (MSMEs), the gap between conventional financial institutions and Islamic financial institutions, and the limited understanding of MSMEs regarding sharia-based financial aspects. This study aims to identify strategies to improve MSME actors’ understanding of Islamic finance as an effort to enhance MSME performance in Rondaman Village. This study employed a descriptive qualitative method with SWOT analysis as the data analysis technique. The results showed that improving Islamic financial literacy in enhancing MSME performance in Rondaman Village, North Padang Lawas Regency, can be carried out through the implementation of the SO (Strength–Opportunity) strategy, namely by utilizing the Muslim-majority population to strengthen Islamic financial institutions, increasing MSME actors’ understanding of riba, developing businesses based on sharia principles, and optimizing the use of access to information. These findings affirm that strengthening Islamic financial literacy is an important strategy in supporting the development of MSME performance based on sharia principles.